1988
DOI: 10.1897/1552-8618(1988)7[715:saiaic]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Structural Alterations in Aquatic Insect Communities Exposed to Copper in Laboratory Streams

Abstract: The effects of copper on aquatic insect communities were examined using rock-filled trays colonized in the field for 30 d, transferred to laboratory streams, and dosed with CuSO4. Each stream was randomly assigned to one of three treatments: control (0 pg/L), low dose (15-32 pg/L), and high dose (135-178 pg/L). Experiments were replicated over three seasons. Exposure to copper for 96 h significantly reduced both the total number of individuals and number of taxa during each season, with greatest effects observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Responses of benthic communities to heavy metals in these chronic mesocosm experiments were generally similar to those reported from field studies of metal-polluted streams in North America [25,26], Europe [27], and New Zealand [3], and in North American laboratory experiments [28][29][30]. Specifically, mayflies and some stoneflies were sensitive, and caddisflies and chironomids were relatively tolerant of metal exposure.…”
Section: Discussionsupporting
confidence: 76%
“…Responses of benthic communities to heavy metals in these chronic mesocosm experiments were generally similar to those reported from field studies of metal-polluted streams in North America [25,26], Europe [27], and New Zealand [3], and in North American laboratory experiments [28][29][30]. Specifically, mayflies and some stoneflies were sensitive, and caddisflies and chironomids were relatively tolerant of metal exposure.…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, the low 48-h EC50 value for altered activity patterns presented here for H. angustipennis (17 g/L) may be indicative of chronic effects, because in life-cycle tests with the caddisfly Clistoronia magnifica, Nebeker et al [45] demonstrated a significant reduction in adult emergence at 13 g Cu/L and a prevented life-cycle completion at 17 g Cu/L. Based on monitoring studies, it is known that concentrations as low as 12 to 32 g Cu/L strongly reduce the abundance and diversity of aquatic insect species [46,47]. In addition, the isopod Asellus aquaticus appeared to be unable to survive during chronic exposure to 5 g Cu/L [48], and the midge Polypedilum nubifer exhibited a decreased emergence at 10 g Cu/L [49].…”
Section: Discussionmentioning
confidence: 99%
“…These toxic acids and metals flow to surface waters, where the acid is eventually neutralized, causing metals to precipitate and coat streambeds with metal oxides, impairing habitat and adversely affecting water quality in over 13,000 mi of U.S. rivers [1]. The biotic effects associated with AMD impacted surface waters include acute impairment of benthic and fish communities as a result of low pH and elevated levels of dissolved heavy metals [2][3][4][5]. A decrease in benthic macroinvertebrate diversity and an increase of tolerant organisms are also often associated with heavy metal pollution in streams.…”
Section: Introductionmentioning
confidence: 99%